2000
DOI: 10.1001/archneur.57.6.824
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Polymorphism and Alzheimer Disease

Abstract: This first report of APOE*E4 and AD from the Indian subcontinent shows very low prevalence of AD in Ballabgarh, India, but association of APOE*E4 with AD at similar strength in Indian and US samples. Arch Neurol. 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
159
2
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(172 citation statements)
references
References 36 publications
(19 reference statements)
9
159
2
2
Order By: Relevance
“…Data are presented as means ± SEM. * P<0.01 vs control (SHAM) and STZ-induced group, ANOVA followed by Tukey's test 2000) and the number of AD patients between 70 and 79 years of age living in India is approximately four times less than the population of people of the same age living in the United States (Ganguli et al 2000). In fact, accumulating cell culture and animal model data show that dietary CUR is a strong candidate for use in the prevention or treatment of major disabling agerelated neurodegenerative diseases (Cole et al 2007).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Data are presented as means ± SEM. * P<0.01 vs control (SHAM) and STZ-induced group, ANOVA followed by Tukey's test 2000) and the number of AD patients between 70 and 79 years of age living in India is approximately four times less than the population of people of the same age living in the United States (Ganguli et al 2000). In fact, accumulating cell culture and animal model data show that dietary CUR is a strong candidate for use in the prevention or treatment of major disabling agerelated neurodegenerative diseases (Cole et al 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Aggregation of misfolded proteins that contain Aβ has been shown to initiate oxidative stress and inflammation and also to be responsible for the neurodegenerative changes and clinical properties of AD (Klein et al 2001). The ICV STZ model appears to produce cognitive deficits similar to those seen in SAD-type dementia (Hong and Lee 1997;Ganguli et al 2000;Salkovic-Petrisic and Hoyer 2007). The ICV STZ model mimics AD because of the cognitive impairment created by STZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research demonstrated that CTS improved the cognitive ability and promoted APP metabolism involving the non-amyloidogenic product pathway in rat cortical neuronal cells. Moreover, as the Indian diet is rich in herbs and spices, the incidence of Alzheimer's disease in India is considerably low (9,10). However, the precise molecular mechanisms of the therapeutic effects of medicinal herbs and spices are largely undefined, and limited data and a small body of convincing evidence exist at the molecular level (11).…”
Section: Introductionmentioning
confidence: 99%
“…As the Indian diet is rich in certain spices, the prevalence of AD patients in India is considerably low (3). However, the precise molecular mechanism for the effect of these spices is largely undefined, and limited data and evidence have been provided at the molecular level (4).…”
Section: Introductionmentioning
confidence: 99%